Left Ventricular Assist Device Implantation Combined with Bentall Procedure - Gode,Safa (2019)
Abstract Ventricular assist devices (VADs) are an important technological development for patients with end-stage heart failure, and approximately 50% of these patients require various additional cardiac procedures. Here we presente the case of a patient suffering from severe aortic insufficiency, aortic root dilatation, and an ascending aortic aneurysm with end-stage decompensated heart failure. We performed the Bentall procedure combined with a left VAD implantation during the same session. The postoperative period was uneventful for this patient, and he was discharged on the 32nd postoperative day. The heart failure symptoms of the patient are reasonable, and he is still on the heart transplantation waiting list.